The evolution of accommodation capacity of agotourist guesthouses in the period 2005-20011 in the Neamţ County - Romania - Nicolae-Gabriel Ursuinu; Manea Drăghici (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
This paper considers the analysis and development capacity of tourist accommodation among ago tourist guesthouses in Neamţ County during 2005-2011. There were taken into account and analyzed indicators such as agro tourist guesthouses in the total accommodation structures, available capacity within agro tourist guesthouses in the total accommodation structure (in number of seats), accommodation capacity in operation in agro tourist guesthouses in all structures of accommodation in Neamţ County (expressed in number of seats-days). Thus it appears that during 2005-2011 the highest rate of agro tourist guesthouses was in 2009 where from the total of 187 accommodation units agro tourist guesthouses had a total of 115 respectively 61.49%; the existing accommodation capacity within agro tourist guesthouses in the total accommodation structures in Neamţ County during 2005-2011 (expressed in number of seats) has also peaked in 2009 through a number of 1709 agro tourist guesthouses from a total of 5446 accommodation structures; the highest value in the number of places-days within agro tourist guesthouses is met in 2009 where from a total number of 1,563,148 seats-days in the county, agro tourist guesthouses represented 30.12% of these namely 470,885. There are analyzed the ways of implementing the local Plan for sustainable development of Neamţ County for 2007-2013.
Keywords: 330; tourism; agro tourist guesthouses; Neamţ County; annual growth rate